Remnant cholesterol and atherosclerotic cardiovascular disease: Metabolism, mechanism, evidence, and treatment - Wang, Kexin; Wang, Rui; Yang, Jiaxin; Liu, Xiaoli; Shen, Hua; Sun, Yan; Zhou, Yujie; Fang, Zhe; Ge, Hailong (Frontiers in Cardiovascular Medicine, 2022)
This review aimed to summarize the evidence of elevated remnant cholesterol and the risks of atherosclerotic cardiovascular disease (ASCVD) and to search for further guidance in clinical therapy. The lipids-lowering treatments such as statins and ezetimibe targeted on low-density lipoprotein cholesterol (LDL-C) have always been the first-line therapy for ASCVD. However, even after statins or new lipid-lowering drugs lowered low-density lipoprotein cholesterol to recommended concentrations, and with other risk factors well-controlled, such as high blood pressure, the risks of developing ASCVD remained. Remnant cholesterol (RC) referred to the cholesterol contained in all remnant lipoprotein particles, which was the cholesterol in the hydrolyzed very-low-density lipoprotein and intermediate-density lipoprotein in the fasting state, and the cholesterol in the chylomicron remnants in the postprandial state. Evidence from in-vitro and animal pathogenic mechanisms studies, epidemiology, and genetic studies all indicated that RC played an important role in predicting the incidence of ASCVD. As a new indicator to reflect atherosclerosis, especially when LDL-C has been controlled to a recommended level, RC was considered as a priority treatment target for people at high risk of ASCVD. The use of statins, fibrates, APOC3 inhibitors, PCSK9 inhibitors, and omega-3 fatty acids to reduce remnant cholesterol levels in the plasma may provide long-term benefits. However, the standardized detection of RC was still controversial, and more studies on appropriate treatments of elevated RC are urgently needed. These positive trials may benefit more patients at high ASCVD risks worldwide in the future.